The Reality of Rural Crime: The unintended consequences of rural policy in the co-production of badger persecution and the illegal taking of deer - Goodall, Orlando (The British journal of criminology, 2021)
Rural policy has produced the unintended consequences of illegal deer taking and the persecution of badgers in the rural West Country of England. This article directs attention towards the mechanisms of social relations between unregulated industry operatives, rural networks and entrepreneurial premises. Accordingly, the offending process is shown to be one of ‘illicit enterprise’, accomplished for instrumental gain through interdependencies between licit and illicit endeavours—practices that emerge synergistically, upon interaction with wider geo-historical conditions. Crucially, illicit activity is shown to be heavily context dependent, contingencies that generate unanticipated outcomes that are peculiar to the tendencies of the South West. Distal conditions are inserted into the explication to posit the antecedent contexts that inadvertently enable the illegal killing of animals.